Vibration control of smart base-isolated irregular buildings using neural dynamic optimization model and replicator dynamics. (1st February 2018) - Gutierrez Soto, Mariantonieta; Adeli, Hojjat
Highlights: A method is presented for hybrid vibration control of smart base-isolated structures. Replicator dynamics from the evolutionary game theory is employed as a resource allocation algorithm to determine control decisions in real-time. A multi-objective optimization is employed using the neural dynamics model of Adeli and Park to obtain the Pareto optimal replicator parameters. The efficacy of the model is demonstrated by application to an 8-story irregular steel-framed building benchmark problem subjected to near-fault historical earthquakes. The performance of the proposed methodology is evaluated and compared with other control algorithms. The methodology can be used to investigate the trade-off between the maximum control force/required energy use and minimum floor accelerations. Abstract: Vibration control of irregular structures subjected to earthquake excitations is a complex civil engineering problem. Base isolation has been used as an earthquake-protective system over the past few decades. It is, however, a passive control system lacking the adaptability to the real-time changes in motion from the earthquake excitation. In order to aid the base isolation system, control devices are installed at the base to provide the real-time vibration control. This research is motivated by evolutionary game theory and uses replicator dynamics as a resource allocation algorithm to determine control decisions. The control algorithm is evaluated using a three-dimensional base-isolated benchmark structure subjected to major historical earthquakes.